What Could ASEAN Learn about Bankruptcy Law from ASEAN Partner Countries, China and Japan? - Suwinto Johan; Amad Sudiro; Ariawan Gunadi (Hasanuddin Law Review, 2022)
By 2021, Japan will have the third-largest economy in the world, behind China, which is currently the world's second-largest economy. China accounts for 17.9% of the global gross domestic product (GDP), while Japan accounts for 5.4 percent. In 2022, the Association of Southeast Asian Nations (ASEAN) and Asia Pacific countries, such as Australia, will establish the RECP (Regional Comprehensive Economic Partnership), becoming the world's largest free trade area cooperative bloc. On the other hand, it brings within several investment risks. Undertakings succumbing in the financial hardships or financial default will be manifested. Diverse legal systems result in different approaches to resolving defaulted businesses. For businesspeople, this disparity in the legal system creates legal uncertainty. The goal of this study is to describe how the bankruptcy system works in RCEP member countries and what ASEAN nations may do to improve their bankruptcy laws. The normative legal method is used in this study. This method compares the legal systems of the top ASEAN countries and other RCEP members. This analysis concludes that ASEAN bankruptcy legislation can be improved by using current systems from other ASEAN and RCEP nations. When faced with bankruptcy, the consistency of regulations is supposed to give legal certainty for corporate actors. This will also provide investors from other countries with a sense of security.